Energy, technology change and the environment : Latin America and the Caribbean in a world context through 2010. - TRINDADE, Sergio C. (1992)
Notes that major obstacles to energy initiatives in support of development are the lack of equitable decision-making capacity with respect to the environment and new technologies, mounting environmental concerns, increased capital costs of energy, and limited investment capacity.